Spiritualia and pastoralia - Erasmus, Desiderius, -1536 (Erasmus, Desiderius, -1536. Works. 1974, 1999)
Ten pieces of Erasmus' writing on spiritual and pastoral topics. The highlight of the volume is the long-awaited translation of Institution of Christian Matrimony.